Cyanobacterial NDH-1 Complexes - Hualing, Mi (Frontiers in Microbiology, 2022)
Light reaction of photosynthesis is efficiently driven by protein complexes orderly arranged in the thylakoid membrane. As 5th complex, NAD(P)H dehydrogenase complex (NDH-1) is involved in cyclic electron flow around photosystem I to protect plants against environmental stressed for efficient photosynthesis. In addition, two kinds of NDH-1 participate in CO2 uptake for CO2 concentration mechanism in cyanobacteria. Recent years, great progress has been made in the assembly and the structure of NDH-1. However, the regulative mechanism of NDH-1 in photosynthesis remains largely unknown. Therefore, understanding the mechanism of NDH-1 is of great significance to reveal the mechanism of efficient photosynthesis. In this review, I introduce current progress on the research of cyanobacterial NDH-1. Finally, I summarize the possible mechanism of cyanobacterial NDH-1 in photosynthesis and discuss the research prospect.